Efektivitas Nurse-Led Transitional Care Terhadap Kejadian Rawat Ulang Dan Kualitas Hidup Pasien Dewasa Pascaperawatan - Mohammad Dwi Ardianto; Novita Elliyana Anisyarina; Shanti Widiyatika I.S; Vidya Nur Utami; Umuhani Umuhani; Bandung Armagedon Pule; Dwi Aghita Widoyani H. (Jurnal Syntax Fusion, 2026)
Nurse-led transitional care is an important nursing strategy to ensure continuity of care after hospital discharge, especially among adult patients with chronic diseases who are at risk of readmission and decreased quality of life. This literature review aimed to analyze the effectiveness of nurse-led transitional care in reducing hospital readmission and improving the quality of life of adult post-discharge patients. The method used was a literature review by analyzing 18 relevant articles published between 2017 and 2025, consisting of Indonesian and international studies. The literature focused on transitional care, discharge planning, readmission, rehospitalization, discharge readiness, self-care, and quality of life. The findings showed that nurse-led transitional care, particularly through structured discharge planning, patient and family education, follow-up after discharge, home visits, telephone counseling, and electronic-based monitoring, contributed positively to reducing readmission, improving discharge readiness, increasing self-care ability, strengthening medication adherence, and improving patients’ quality of life. The strongest evidence was found in patients with stroke, diabetes mellitus, heart failure, and chronic diseases. However, the implementation of discharge planning in several health care facilities remains suboptimal due to limited documentation, high nursing workload, lack of standardization, and insufficient continuity of post-discharge follow-up. Therefore, structured, patient-centered, family-involved, and nurse-led transitional care should be strengthened as part of nursing services to improve patient outcomes and health service efficiency.